Definitive hematopoietic stem/progenitor cells manifest distinct differentiation output in the zebrafish VDA and PBI - Jin, Hao (Company of Biologists, 2009)
One unique feature of vertebrate definitive hematopoiesis is the ontogenic switching of hematopoietic stem cells from one anatomical compartment or niche to another. In mice, hematopoietic stem cells are believed to originate in the aorta-gonad-mesonephros (AGM), subsequently migrate to the fetal liver (FL) and finally colonize the bone marrow (BM). Yet, the differentiation potential of hematopoietic stem cells within early niches such as the AGM and FL remains incompletely defined. Here, we present in vivo analysis to delineate the differentiation potential of definitive hematopoietic stem/progenitor cells (HSPCs) in the zebrafish AGM and FL analogies, namely the ventral wall of dorsal aorta (VDA) and the posterior blood island (PBI), respectively. Cell fate mapping and analysis of zebrafish runx1(w84x) and vlad tepes (vlt(m651)) mutants revealed that HSPCs in the PBI gave rise to both erythroid and myeloid lineages. However, we surprisingly found that HSPCs in the VDA were not quiescent but were uniquely adapted to generate myeloid but not erythroid lineage cells. We further showed that such distinct differentiation output of HSPCs was, at least in part, ascribed to the different micro-environments present in these two niches. Our results highlight the importance of niche in shaping the differentiation output of developing HSPCs.